GENERIC PRESCRIPTION IN INDIA – A REVIEW - M, VIGNESH; GNK, GANESH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
In India, a Generic drug plays a major role where most of the people afford and depend on it, due to the budget-friendly and easily available widely. However, some of the pharmaceutical manufacturer’s license was terminated due to the unsold or banned products of branded drugs, which are manufactured in USFDA as small plants, were manufactured in India without the approval. There were many misconceptions with the manufacturers, for following the right strategy to bring generic medications, clearing data integrity issues, sales, and marketing aspects of drugs for the successful outcome. India has also been subject to increasing inspections by global regulatory bodies in recent times. There has been an increase in enforcement actions taken by regulatory bodies for cases related to data integrity. From this review, it concluded that what are the current trends involved in the generic drugs and their category based on the license, impact, and issues involved and also provides the recommendations to be followed to prevent further issues in the future.